2022
DOI: 10.1002/mrc.5260
|View full text |Cite
|
Sign up to set email alerts
|

Computational1H and13C NMR in structural and stereochemical studies

Abstract: Present review outlines the advances and perspectives of computational 1H and 13C NMR applied to the stereochemical studies of inorganic, organic, and bioorganic compounds, involving in particular natural products, carbohydrates, and carbonium ions. The first part of the review briefly outlines theoretical background of the modern computational methods applied to the calculation of chemical shifts and spin–spin coupling constants at the DFT and the non‐empirical levels. The second part of the review deals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 389 publications
(776 reference statements)
0
28
0
Order By: Relevance
“…As recently reviewed by both Kupka [ 22 ] and Krivdin, [ 23 ] applied computational chemistry for predictions of NMR chemical shifts and coupling constants has been reported in the literature with dramatically increasing frequency to aid in resonance assignments, stereochemical determinations, and overall structure confirmation. In particular, DFT calculations present an ideal trade‐off in terms of accuracy versus molecular size, and calculations of moderately sized molecules are accessible on personal computers in less than 1 day of overall calculation time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently reviewed by both Kupka [ 22 ] and Krivdin, [ 23 ] applied computational chemistry for predictions of NMR chemical shifts and coupling constants has been reported in the literature with dramatically increasing frequency to aid in resonance assignments, stereochemical determinations, and overall structure confirmation. In particular, DFT calculations present an ideal trade‐off in terms of accuracy versus molecular size, and calculations of moderately sized molecules are accessible on personal computers in less than 1 day of overall calculation time.…”
Section: Resultsmentioning
confidence: 99%
“…As clearly shown in the expansion of the 1,1-ADEQUATE spectrum in Figure 3, a strong 1 J CC correlation was observed between H-6 and the downfield carbonyl signal at 180 ppm, whereas no correlation was observed to the signal at 169 ppm. Thus, the signal assignments for the β-lactam carbonyl and proximal carboxylate again need to be swapped in the original NMR structural report for imipenem by Ratcliffe et al [8] As recently reviewed by both Kupka [22] and Krivdin, [23] applied computational chemistry for predictions of NMR chemical shifts and coupling constants has been reported in the literature with dramatically increasing frequency to aid in resonance assignments, stereochemical determinations, and overall structure confirmation. In particular, DFT calculations present an ideal trade-off in terms of accuracy versus molecular size, and calculations of moderately sized molecules are accessible on personal computers in less than 1 day of overall calculation time.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this study, the unexpectedly high rates of reaction between the alkyllithium reagents and amides, as compared with esters and ketones, were observed. The 7 Li and 19 F NMR investigation of the reaction of 4-fluorophenyllithium 7 Li NMR spectra of n-BuLi and the mixed tetramers between n-BuLi and n-BuOLi in the 1:3 THF-Me 2 O solution (0.03 M) at À130 C. Reproduced with minor editing privilege from Reich [4] with the permission of the American Chemical Society F I G U R E 1 1 6 Li and 13 C NMR spectra of the PMDTA titration of the 0.14 M solution of 8 in 3:2:1 THF/Me 2 O/Et 2 O at À141 C. Reproduced with minor editing privilege from Jantzi et al [36] with the permission of the American Chemical Society (monomeric 21 and dimeric 22) and benzoate ester revealed two reactive intermediates, a homodimer of the tetrahedral intermediate (23), which was stable below À100 C, and a mixed dimer (24), which was stable at higher temperatures. Direct formation of dimers suggested that the ArLi dimer might be the reactive aggregate rather than the usually more reactive monomer, as shown below.…”
Section: Recent Resultsmentioning
confidence: 99%
“…At present, we are witnessing an unprecedentedly fast development of theoretical and computational methods in the field of NMR spectroscopy, [10,11] in parallel with marked progress in modern NMR technique and instrumentation. In this line, NMR-oriented calculations at different levels of theory [12][13][14][15][16][17][18][19][20] for the most common 1/2 spin NMR isotopes-proton, [21][22][23] carbon, [24][25][26][27] nitrogen, [28] fluorine, [29] silicon, [30] phosphorus, [31,32] and Reproduced with minor editing privilege from Alam et al [5] with the permission of the American Chemical Society selenium, [33] are in their mature period. In contrast, computational lithium NMR is now only in its infancy.…”
mentioning
confidence: 99%
“…The 59 Co isotope has 100% natural abundance and its chemical shift range is extremely wide, being about 20,000 ppm [ 8 ], which is the largest among the known NMR scales. In this regard, accurate theoretical predictions of the NMR chemical shifts provide a powerful tool for the structural elucidation of organic and bioorganic molecules, transition metal complexes, and related species [ 9 , 10 , 11 , 12 , 13 ]. In this respect, NMR chemical shifts, nitrogen and cobalt in particular, represent an undoubted challenge [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%